2017
DOI: 10.1021/acs.jpcc.7b08125
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Effects of Cu Component and the Promoter on the Selectivity and Activity for Efficient Removal of Acetylene from Ethylene on Cu-Based Catalyst

Abstract: The selective hydrogenation of C2H2 on five types of Cu(0)/Cu­(I), Cu(0), Cu­(I), PdCu(0), and PdCu­(I) catalysts are investigated to illuminate the effects of Cu component and the promoter on the selectivity and activity toward C2H4 formation. The selectivity and activity toward C2H4 formation on five types of catalysts are examined using density functional theory calculations. The results indicate that Cu(0)/Cu­(I) bicomponent catalyst presents higher selectivity but significantly lower activity toward C2H4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 75 publications
1
10
2
Order By: Relevance
“…In this study, when the route of C 2 H 4 desorption is favored, the energy difference between C 2 H 4 desorption and its hydrogenation as the simplest descriptor is employed to quantitatively evaluate C 2 H 4 selectivity. Meanwhile, the rate of C 2 H 4 formation is calculated to evaluate the activity of C 2 H 4 formation, , which is calculated according to the two-step model , under the typical experimental conditions ( T = 425 K, P = 1 atm; H 2 /C 2 H 2 = 10/1, the partial pressures of C 2 H 4 , H 2 , and C 2 H 2 correspond to 0.89, 0.1, and 0.01 atm, respectively). The details about the definition of activity and selectivity of C 2 H 4 formation are presented in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, when the route of C 2 H 4 desorption is favored, the energy difference between C 2 H 4 desorption and its hydrogenation as the simplest descriptor is employed to quantitatively evaluate C 2 H 4 selectivity. Meanwhile, the rate of C 2 H 4 formation is calculated to evaluate the activity of C 2 H 4 formation, , which is calculated according to the two-step model , under the typical experimental conditions ( T = 425 K, P = 1 atm; H 2 /C 2 H 2 = 10/1, the partial pressures of C 2 H 4 , H 2 , and C 2 H 2 correspond to 0.89, 0.1, and 0.01 atm, respectively). The details about the definition of activity and selectivity of C 2 H 4 formation are presented in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Dissociation of H 2 , DMO, and MG. H atoms derived from H 2 dissociation are essential for DMO hydrogenation. Zhang et al 34 reported that the H 2 dissociation is spontaneous to form the adsorbed H atom on Cu-based catalysts. However, they also reported that an amount of molecularly adsorbed H 2 also exists.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…C 2 H 4 selectivity is evaluated by the energy difference between the hydrogenation of C 2 H 4 and the adsorption of C 2 H 4 , which is calculated using eq , As shown in eq , Δ G a corresponds to the activation free energy of hydrogenation routes (the C 2 H 4 intermediate or CHCH 3 intermediate route) and G ads corresponds to the activation free energy of the C 2 H 4 adsorption route; when the value of G sel is more positive and larger, which represents that C 2 H 4 more easily undergoes desorption to form gaseous C 2 H 4 instead of ethane formed by C 2 H 4 successive hydrogenation, the catalyst exhibits good C 2 H 4 selectivity.…”
Section: Resultsmentioning
confidence: 99%